A study on how environmental issues are discussed in social studies textbooks - Seker, Mustafa (SPRINGER, 2024)
Environmental education should be sustainable. For a peaceful and happy world, each country is expected to see the environment as common heritage and to bring this sensitivity to the students in the education processes. Social Studies course is a course that aims to educate students to be effective, sensitive to living together, and have a perception of common heritage within the framework of global citizenship. For the environmental sensitivity to be more effective, the education process is bound to carry out very important tasks. Students can be supported to gain awareness of environment through educational programs, textbooks, teaching strategies, methods, and techniques from an early age on and throughout their education. The aim of this study is to investigate what kind of educational process the students in Turkey, which has an important geopolitical position in the world, go through in the social studies course, which bears the responsibility of conveying universal principles. In our study, the mixed method was used and it was investigated whether the environmental issues are discussed in social studies textbooks in accordance with the developmental levels of the students. In the research process, teachers' opinions as well as the textbooks were examined. As a result of the research, it has been understood that social studies textbooks do not primarily handle the environmental issues efficiently and that children are not trained well enough to gain environmental sensitivity.
Keywords: Education; Environmental education; Social studies; Textbook; Development periods; Science & Technology - Other Topics; Environmental Sciences & Ecology